NOGLE TANKER OMKRING FLYTNING - Ramløv, Kirsten (Tidsskriftet Antropologi, 2001)
The process of moving objects or belongings from one place to another very often implies the necessity of selection. This article deals with two very different situations of moving. The first one concerns the complete removal of objects from the Ethnographic Collection during the rebuilding of the National Museum in Copenhagen in the early 1990’s and the subsequent reorganisation of them in the new permanent exhibitions. The second situation is an ordinary change of address. In the museum situation, the necessity of selection did not occur until decisions were made as to which objects were to be displayed in order to reflect cultural themes of the region in question. In the situation of the change of address, the selecting process started immediately. Because of the representative and communicative potentials of objects, considerations of identity usually accompanied the choices, whether, as in the first case, the identity of the objects concerned a cultural universe, or, as in the second case, was connected with a person.